Does Distributed Leadership Affect the Performance of Schools in England? - Dalton, Pedro (2005)
The 'modernisation agenda' of the incumbent Labour government increasingly looks towards the private sector to provide a panacea for public sector woes. Nowhere is this more apparent than in the education where the National College for School Leadership has been created with the remit of creating 'a single national focus for school leadership development and research'.